THE INFLUENCE OF BRAND EXPERIENCE, BRAND IMAGE AND AFFECTIVE COMMITMENT TO BRAND LOYALTY OF BANK SULUTGO CUSTOMERS IN MANADO CITY, INDONESIA - Mongisidi R. Sanny; Willem J.F. Alfa Tumbuan; Jessy J. Pondaag (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The purpose of this research is to determine the influence of brand experience, brand image, and affective commitment on brand loyalty in Bank SulutGo Manado customers, both simultaneously and partially. Data collection in this research used a questionnaire with a total of 400 respondents who were customers of Bank SulutGo Manado. The results of this research show that there is a significant influence of brand experience, brand image, and affective commitment on brand loyalty. Based on the results of this research, Bank SulutGo must continue to maintain a good reputation, promote the company more, and have other superior products so that in the future it can further influence brand loyalty among customers, continue to provide good and safe service and continue to pay attention to the environment around the Bank. SulutGo must continue to increase brand loyalty directly, as well as continue to maintain the quality of their service which can have a positive influence on customer affective commitment so that they can continue to increase brand loyalty among customers